Citrate Promotes Excessive Lipid Biosynthesis and Senescence in Tumor Cells for Tumor Therapy. Issue 1 (7th November 2021) - Zhao, Yangjing; Liu, Xia; Si, Fusheng; Huang, Lan; Gao, Aiqin; Lin, Wenli; Hoft, Daniel F.; Shao, Qixiang; Peng, Guangyong
Abstract: Metabolic disorder is one of the hallmarks of cancers, and reprogramming of metabolism is becoming a novel strategy for cancer treatment. Citrate is a key metabolite and critical metabolic regulator linking glycolysis and lipid metabolism in cellular energy homeostasis. Here it is reported that citrate treatment (both sodium citrate and citric acid) significantly suppresses tumor cell proliferation and growth in various tumor types. Mechanistically, citrate promotes excessive lipid biosynthesis and induces disruption of lipid metabolism in tumor cells, resulting in tumor cell senescence and growth inhibition. Furthermore, ATM‐associated DNA damage response cooperates with MAPK and mTOR signaling pathways to control citrate‐induced tumor cell growth arrest and senescence. In vivo studies further demonstrate that citrate administration dramatically inhibits tumor growth and progression in a colon cancer xenograft model. Importantly, citrate administration combined with the conventional chemotherapy drugs exhibits synergistic antitumor effects in vivo in the colon cancer models. These results clearly indicate that citrate can reprogram lipid metabolism and cell fate in cancer cells, and targeting citrate can be a promising therapeutic strategy for tumor treatment. Abstract : Reprogramming of metabolism is a novel strategy for cancer treatment. Extracellular citrate administration in tumor cells induces activation of the DNA damage response, MAPK, and mTOR signaling pathways. The activated cascades further induce excessive lipid biosynthesis and provoke senescence to impair tumor cell growth in vitro and in vivo. Targeting citrate can be a promising therapeutic strategy for tumor treatment.